The Criminal Pre-Trial System from a Human Rights Perspective - Ananda Nasirah; Hadi Tuasikal; A. Sakti R.S. Rakia (Journal of Law Justice (JLJ), 2025)
The purpose of this research is to examine how the pretrial criminal system supervises and evaluates the legality of actions taken by law enforcement officials from a human rights perspective and to identify the factors influencing the pretrial system. The method used in this study is normative legal research with a legislative approach, analyzing laws and regulations related to the pretrial process. The novelty of this research lies in the pretrial system, which has not been extensively studied due to the arbitrariness of law enforcement officials, as well as an analysis of the implementation of regulations related to pretrial matters. The findings of this study indicate that the pretrial system has the authority to examine evidence and act proactively; in this case, the pretrial can identify abuses of process or violations of human rights at an early stage. This procedure aims to protect the human rights of innocent individuals. The pretrial system also serves to control actions by law enforcement officials that are contrary to human rights. However, there are factors that influence the pretrial criminal system in exercising its authority, which include aspects of substantive law, legal officials, and social society. These aspects are interconnected and cannot be separated. In conclusion, despite the factors influencing the pretrial criminal system, the presence of pretrial proceedings as a means to protect human rights can enhance oversight and accountability in the pretrial process to prevent abuse of power.